“CLASSROOM MANAGEMENT AND ITS IMPACT ON THE ENGLISH LANGUAGE TEACHING-LEARNING PROCESS WITH THE STUDENTS OF “MANUEL JOSÉ RODRIGUEZ” HIGH SCHOOL. MOLACATOS PARISH. ACADEMIC - ARMIJOS MOROCHO, JUAN CARLOS (2011)
This research work entitled: CLASSROOM MANAGEMENT AND ITS IMPACT ON THE ENGLISH LANGUAGE TEACHING LEARNING PROCESS WITH THE STUDENTS OF THE HIGH SCHOOL MANUEL JOSÉ RODRÍGUEZ, MALACATOS PARISH. ACADEMIC YEAR 2009- 2010, whose general objective was: to determine the impact of the classroom management in the English language teaching learning process, has been developed with the purpose of discovering if teachers use classroom management techniques, to achieve a good atmosphere for the learning of the English language. To achieve this, we have used some methods, such as the scientific, descriptive, deductive, analytic and contrastive, the same ones that have served us to develop the present research work of the best way. To collect the information of the researched institution, we used the survey technique. It was applied to three teachers and one hundred eight students. Moreover we used the observation to see the different management techniques that teachers use. Then to represent the obtained data we used the descriptive statistics, which let us present the information on graphs and charts, for an easier understanding. The results of this research work are: that there is little use of the classroom management techniques, and that the teachers and students do not develop their roles as they should make it, into the English Language Teaching Learning Process, so that they have not got a good learning.